Effect of felodipine on myocardial and renal injury induced by aldosterone-high salt hypertension in uninephrectomized rats - Matsubara, B.B. [UNESP]; Franco, M.; Janicki, J.S.; Matsubara, L.S. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2010)
It has been recently shown that calcium channel blockers might have a protective effect on cardiac fibrogenesis induced by aldosterone. The objective of this study was to evaluate the protective effect of felodipine, a dihydropyridine calcium channel blocker, against heart and kidney damage caused by aldosterone-high sodium intake in uninephrectomized rats. Wistar rats were divided into three groups: CNEP (uninephrectomized + 1% NaCl in the drinking water, N = 9); ALDO (same as CNEP group plus continuous infusion of 0.75 µg/h aldosterone, N = 12); ALDOF (same as ALDO group plus 30 mg·kg-1·day-1 felodipine in the drinking water, N = 10). All results were compared with those of age-matched, untreated rats (CTL group, N = 10). After 6 weeks, tail cuff blood pressure was recorded and the rats were killed for histological analysis. Blood pressure (mmHg) was significantly elevated (P < 0.05) in ALDO (180 ± 20) and ALDOF (168 ± 13) compared to CTL (123 ± 12) and CNEP (134 ± 13). Heart damage (lesion scores - median and interquartile range) was 7.0 (5.5-8.0) in ALDO and was fully prevented in ALDOF (1.5; 1.0-2.0). Also, left ventricular collagen volume fraction (%) in ALDOF (2.9 ± 0.5) was similar to CTL (2.9 ± 0.5) and CNEP (3.4 ± 0.4) and decreased compared to ALDO (5.1 ± 1.6). Felodipine partially prevented kidney injury since the damage score for ALDOF (2.0; 2.0-3.0) was significantly decreased compared to ALDO (7.5; 4.0-10.5), although higher than CTL (null score). Felodipine has a protective effect on the myocardium and kidney as evidenced by decreased perivascular inflammation, myocardial necrosis and fibrosis.
Keywords: Aldosterone; Dihydropyridine; Fibrinoid necrosis; Vascular remodeling; Hypertension; Myocardial remodeling